Optimization of an MPEG-1 Layer 3 decoder on an ADSP-BF533 - Del Rosario, Manuel Jr. R.
Audio data compression is highly demanded nowadays and the MPEG-1 Layer 3 is one algorithm commonly used for compression of CD quality music. Different decoding algorithms were developed due to the emergence of MP3 music and were applied to different platforms and processors. A hardware implementation considers the amount of memory available and the processing speed. This project aims to further optimize the available algorithm in terms of computational complexity, memory management, and accuracy by looking into the most computationally intensive blocks of the decoder namely; Huffman decoding block, requantization block, IMDCT block and the polyphase filter bank. Different implementation of these blocks were applied, tested and simulated on an ADSP-BF533 Blackfin DSP. the MP3 decoder underwent testing to ensure full compliance according to the ISO standards. After optimization, ISO Compliance was achieved having an RMS Error equal to 8.60199e-06 and MAx Absolute Error equal to 1.54973e-05.